Problemas sociales y COVID-19 - Gonzales-García, Carlos Ricardo (2021)
In the present century, humanity has witnessed how numerous infectious diseases threatened society and our own lives. Unfortunately, a highly unstoppable new virus has appeared, crossing countries and continents, spreading rapidly between humans. The uncertainty generated by COVID-19 and its fatal results, given the prevalence of the media, including social networks, has spread fear to all populations, judging by the online reactions and experiences of others towards the pandemic. Another case, which is added to the discussion, was the presence of malicious actors who used these networks to covertly affect unconscious behavior with disinformation (Bastick, 2021).